Antiplatelet therapy and outcome in COVID-19: the Health Outcome Predictive Evaluation Registry. Issue 2 (5th October 2021) - Santoro, Francesco; Nuñez-Gil, Ivan Javier; Vitale, Enrica; Viana-Llamas, Maria C; Reche-Martinez, Begoña; Romero-Pareja, Rodolfo; Feltez Guzman, Gisela; Fernandez Rozas, Inmaculada; Uribarri, Aitor; Becerra-Muñoz, Víctor Manuel; Alfonso-Rodriguez, Emilio; Garcia-Aguado, Marcos; et al.
Abstract : Background: Standard therapy for COVID-19 is continuously evolving. Autopsy studies showed high prevalence of platelet-fibrin-rich microthrombi in several organs. The aim of the study was therefore to evaluate the safety and efficacy of antiplatelet therapy (APT) in hospitalised patients with COVID-19 and its impact on survival. Methods: 7824 consecutive patients with COVID-19 were enrolled in a multicentre international prospective registry (Health Outcome Predictive Evaluation-COVID-19 Registry). Clinical data and in-hospital complications were recorded. Data on APT, including aspirin and other antiplatelet drugs, were obtained for each patient. Results: During hospitalisation, 730 (9%) patients received single APT (93%, n=680) or dual APT (7%, n=50). Patients treated with APT were older (74±12 years vs 63±17 years, p<0.01), more frequently male (68% vs 57%, p<0.01) and had higher prevalence of diabetes (39% vs 16%, p<0.01). Patients treated with APT showed no differences in terms of in-hospital mortality (18% vs 19%, p=0.64), need for invasive ventilation (8.7% vs 8.5%, p=0.88), embolic events (2.9% vs 2.5% p=0.34) and bleeding (2.1% vs 2.4%, p=0.43), but had shorter duration of mechanical ventilation (8±5 days vs 11±7 days, p=0.01); however, when comparing patients with APT versus no APT and no anticoagulation therapy, APT was associated with lower mortality rates (log-rank p<0.01, relative risk 0.79, 95% CI 0.70 to 0.94). On multivariable analysis, in-hospital APT was associated with lower mortality risk (relative risk 0.39, 95% CI 0.32 to 0.48, p<0.01). Conclusions: APT during hospitalisation for COVID-19 could be associated with lower mortality risk and shorter duration of mechanical ventilation, without increased risk of bleeding. Trial registration number: NCT04334291 .